Increased Use of Timber in New Buildings in Oslo and Akershus: Potentials and GHG Emission Effects - Nygaard, Marius; Bashevkin, Isaak Elias Skjeseth; Groba, Ute; Sunter, Catherine (Frontiers in Built Environment, 2019)
ABSTRACT To guide political and industrial priorities, it is vital to estimate the emission effects of increased use of timber in buildings. The article reports on a broad study that had the following aims: 1. To forecast the number, types, floor area and location of new buildings that will be built in Oslo and Akershus counties between 2015 and 2030. 2. To estimate how many of these buildings a) will be and b) could be built with timber as the main construction material. 3. To compare these timber potentials to the availability of locally and sustainably sourced and manufactured timber. 4. To estimate the GHG emission effects of substituting concrete and steel with timber in new buildings. The research is based on official prognoses for population growth. They are combined with building predictions derived from municipal statistics and plans. A GHG reduction factor is extracted from existing studies of the effects of conversion to timber. This factor is used to estimate the GHG saving potentials of different scenarios for timber use. Main results: • The forecast of building numbers, categories, sizes and location is a useful tool when discussing urban, industrial and architectural strategies. • Housing in 2-8 stories, not high-rise buildings, represents the biggest potential for increased use of timber in Norway. • Scientific consensus is not established regarding timber buildings and emissions. Especially the effects of carbon storage in long-lived products and use of residues for biofuel that substitutes fossil fuel are still debated. To convey an order of magnitude, the different emission-saving effects are separated. • The estimates of GHG mitigation indicate that conversion to use of timber may have significant effects, but measures in the transport sector are more important for reaching the emission targets in Oslo and Akershus counties. • To be robust, the argument for timber buildings must include the perspective of a green industrial shift based on renewable resources and innovative technology, design and architecture. • The vicinity of Norway´s biggest market for timber buildings and the country´s largest forests and timber-based industries represents a unique opportunity for sustainable urban and regional development.